Municipal Solid Waste Management: Circular Economy Evaluation in Turkey - Gokkurt Baki, Oylum; ERGUN, Osman Nuri (Environmental Management and Sustainable Development, 2021)
With the increase in environmental negativities according to wastes, priority has been given to sustainable practices and thus the circular economy (CE), that is, the recycling of wastes to the economy, and related zero waste practices have gained priority in Turkey. Turkey produced 32.2 million tonnes of waste overall per year and it means that waste per capita is approximately 1.16 kg per day and also the average recycling rate of all waste in Turkey is 12.3% according to 2018 records of TurkStat. According to these data, 20.24% of the wastes are sent to the municipal garbage disposals, 67.20% is disposed of by the regular storage method and 38% is recycled by composting. Also, according to the 2016 data, wild storage in Turkey continues at 27%. In the present study, the relationships between the yearly population growth, the increase in waste and in disposal facilities, and in the number of waste disposal facilities were examined and some relevant evaluations were made for the coming years. The projections were calculated using the data of Turkey in the coming years, the amount of waste, the amount of recycled waste, and the number of facilities. The recommendations were presented and emphasis was made for the requirements of the application of circular economy in Turkey. As a result, the analysis results obtained showed that the increases in the amount of waste will increase both the amount of waste and the areas where the waste will be disposed of and will create serious problems in the future. A sustainable waste management system and circular economy practices require that recyclable wastes be collected separately at the source, and the recycling process is carried out in a planned structure and if possible, no waste is generated. Collecting wastes separately at the source and public participation and awareness-raising in the zero-waste process is a must for the success of this process.